Estudo dos efeitos n?o lineares de automodula??o de fase e modula??o de fase cruzada em fibras ?pticas - Paiva, Rodrigo Bahia (2003)
In this work some phenomena that occur during the propagation of pulses of light in optical fibers [1], [7], [13], [16], [18], [20], [21], [22], [24], [25], [59] e [60] are studied. The study is based on the Nonlinear Schr?dinger Equation (NLS), gotten in Chapter 2 from the equations of Maxwell, considering a nonlinear susceptibility. The adopted mathematical model for the susceptibility comes from the Kerr Effect, that implies a fiber dependence with the power of the optical field. From this model the refractive index has a linear part that depends on the frequency describes by the dispersive character of the medium, and the nonlinear part that is independent of the frequency. The preservation of the polarization of the incident light on the fiber was still assumed, making possible the use of a scalar model, that is, neglecting the vectorial character of the propagation equation. The NLS equation includes the phenomena of losses, dispersion and the nonlinear effects of Self-Phase Modulation (SPM) and Cross Phase Modulation (XPM) and we presentan analytical solution for some particular cases. In this work the theoretical interpretation of these solutions, in both time and frequency domain is discassed, as well as we check all results with the numerical solutions, gotten from all siABSTRACT. XVI mulations done in the VPI ? (Virtual Photonics Inc. ? Transmission ModulePackage) platform, based on the SSF method shown in Annex B. The emphasis of the work is concentrated on the study of the SPM and the XPM presented, respectively, Chapters 5 and 6. For a well understanding of these phenomena, several results found in the specialized literature, and cited in the list of references, has been reproduced. The effectiveness of these phenomena is reported to the characteristics of the incident light such as: temporal duration and sharp of the pulse, central frequency of the carrier, optical power, besides the characteristics of the optic fiber in the region operation: chromatic dispersion of 1st and 2nd orders, effective area, nonlinear index of refraction and losses. These parameters had been considered in accordance with the available commercially optical fibers data.